The importance of grain legumes for a domestic protein security - Święcicki, Wojciech; Szukała, Jerzy; Rutkowski, Andrzej; Jerzak, Michał; Mikulski, Wojciech; Górynowicz, Barbara (Polish Journal of Agronomy, 2020)
Soya meal is the main high protein source in feeding pigs and poultry. Taking into account the annual value of domestic import, limited soya seed producers (USA, Argentina, Brasil) and China as the main soya seed importer (66 percent of the world import), a use of alternative protein sources (grain legumes, rape meal, DDGS) seems to be justified. An additional reason for a so called protein security in Poland are the feed regulations prohibiting a usage of GM products in feeding. Polish Government launched research projects for two periods (2011–2015 and 2016–2020) to solve main problems related to increased production and usage of domestic protein sources in animals feeding. Main strategies and research results of four areas – grain legume genetics and breeding, cropping technologies, pigs and poultry feeding and economic aspects of production, market infrastructure and turnover of domestic protein crops – are presented in the paper. Satisfactory is an increase of acreage under grain legumes in Poland – from 100 thousand ha in 2011 to 300 thousand ha in 2019. At present, given the availability of domestic grain legumes and rape meal it is possible to decrease soya meal imports up to 60–50 percent. Over the past decade, a strong increase of poultry meat production (about 120 percent) with a rather small increase of soya meal imports (about 18 percent) is also as optimistic tendency. A lasting solution may be achieved by setting a national/ European indicator target that would put the mandatory share of domestic protein sources in feed mixes at 10–20%, and creation of Polish feed companies, competitive to foreign, both large and mobile feed mixing plants, using the farmer’s raw materials.